Social Stratification and Communal Stigma in Ahmad Tohari’s Rumah yang Terang - Fadila (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study aims to analyze the story construction and social structure in Ahmad Tohari’s short story Rumah Yang Terang. This research employs a qualitative method, utilizing a structuralist approach to dissect intrinsic elements and the sociology of literature to understand the represented social realities. Data collection was conducted through close reading and note-taking, followed by content analysis encompassing unitizing, coding, and inferring procedures. The findings indicate that the story's construction serves not only as a narrative framework but also as a medium to represent the tension between tradition and modernity. Sociologically, the short story captures complex social structural dynamics, where patriarchal authority within the family clashes with the hegemonic social control of the rural community. These findings confirm that individual acceptance of modernity is often hindered by communal stigma and established social stratification. This study concludes that Ahmad Tohari successfully codifies rural cultural friction into a concise narrative, reaffirming literature’s position as a reflective social document.